Effect of The Building Maintenance and Resource Management Through User Satisfaction of Maintenance - Pontan, Darmawan; Surjokusumo, Surjono; Johan, Johny; Hasyim, Cholil; Ikhsan Setiawan, Muhammad; Saleh Ahmar, Ansari; Harmanto, Dani (International Journal of Engineering and Technology, 2018)
PD Pasar Jaya manages 153 markets spread across Jakarta. Market building is a place of public services, in order to provide excellent service to the community, it is important to maintain it properly. Maintenance management of PD Pasar Jaya is still far from the expected. The purpose of this study was to determine the effect of directly and indirectly from the condition of the building and maintenance resources to user satisfaction through maintenance management. The research method is by taking a sample of 14 buildings market, then use the check list building condition assessment visually and dissemination of survey questionnaires to 216 respondents, namely the market manager, the kiosk, and visitors. The questionnaire consisted of four variables: the condition of the building (X1), maintenance resources (X2), as an variable, independent maintenance management (Y) as variable, an intervening while user satisfaction (Z) as the dependent variable. Furthermore, assessment data is processed by the descriptive analysis of the building, while the questionnaire survey data processed by path analysis using linear regression with SPSS ver. 22. The results of assessment of 14 buildings is a market average of 78 of the highest value of 100, this means that the condition of the building is being with only minor damage. The total yield of the influence of the condition of the building (42.38%) and maintenance resources (25.01%) towards satisfaction of a user through maintenance management (1.26%) is 68.65%.